Perbandingan Hasil Belajar Matematika Siswa Kelas V yang Bergaya Kognitif Field Dependent dengan Independent - Rahman Rahman; Makmur Nurdin; Rosmalah Rosmalah (STKIP Andi Matappa Pangkep, 2021)
This study is a quantitative study with comparative model that aims to determine whether or not there is a difference between the mathematics learning outcomes of five (5th) grade students of SD cluster I Salomekko district, Bone regency which field dependent and independent cognitive style. The data in this study were collected by GEFT test and learning outcomes tests and processed using descriptive statistical analysis and inferential analysis. The results showed that there was a significant difference between the mathematics learning outcomes of five (5th) grade students of SD cluster I Salomekko district, Bone regency which field dependent and independent cognitive style with tcount (-4,37) is smaller (<) the value of -ttable (-1.988) which means H0 is rejected and Ha is accepted. Based on the results of the study, it can be concluded that there is a difference between the mathematics learning outcomes of fifth grade elementary school students in Cluster I, Salomekko district, Bone regency with field dependent cognitive style and field independent cognitive style. Thus, it can be said that each student has different abilities or cognitive styles. Therefore, the learning outcomes obtained are alsodifferent due to differences in cognitive styles.